Reaction Speed and Coordination Improves The Punch of Gyaku Zuki Chudan - Riyadi, Dani Nur; Lubis, Johansyah; Rihatno, Taufik (Department of Physical Education, Sport, Health and Recreation, 2020)
This study aims to determine the effect of reaction speed, eye-hand coordination towards the gyaku zuki chudan on Bandung Karate Club Athlete in Bekasi City. The research method is a descriptive associative, and the analysis technique is path analysis. The sampling technique used is a total sampling with a sample amount of 16 people. The instruments used are a test of gyaku zuki chudan, reaction speed measurement using Catch the ruler test, eye-hand coordination measurement using throw-catch the ball, The amount of value obtained by gyaku zuki chudan technique is to do a straight punch parallel to the chest or angle of the 90Ã‚Â° with as soon as possible for 10 seconds. Samples tested 2 times, performed in a closed room, the results obtained in the execution of the test is hitting in the size of the number of punch. The conclusions are: (1) reaction speed directly affects on the gyaku zuki chudan, and (2) eye-hand coordination directly affects on the gyaku zuki chudan.